2019
DOI: 10.1093/pm/pnz218
|View full text |Cite
|
Sign up to set email alerts
|

Apps for Older People’s Pain Self-Management: Perspectives of Primary Care and Allied Health Clinicians

Abstract: Background Chronic arthritic pain is one of the major causes of physical suffering and disability among older people. Primary care and allied health clinicians use various approaches to help their older clients better manage their arthritic pain. The growing uptake of technology among older people offers the potential for clinicians to integrate an arthritic pain app into their patients’ self-management plans. This study explored the perspectives of Australian primary care and allied health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The opinions of older people with chronic pain regarding an mHealth intervention via a smartphone suggested the importance of information sharing, including education to support self-care and self-administration of analgesia [ 53 ]. Five of the qualitative studies were pilot or feasibility studies with either service users or health professionals [ 44 , 45 , 47 , 48 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The opinions of older people with chronic pain regarding an mHealth intervention via a smartphone suggested the importance of information sharing, including education to support self-care and self-administration of analgesia [ 53 ]. Five of the qualitative studies were pilot or feasibility studies with either service users or health professionals [ 44 , 45 , 47 , 48 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Older users found it beneficial to have associated input from their clinicians to establish and reinforce the use of technology or a pain self-management app [ 43 , 45 , 46 ]. Clinicians themselves expressed concern that not all service users or the clinicians responsible for their care would be willing to embrace new technology [ 43 , 44 , 48 ]. The importance of clinicians’ engagement with and confidence in the use of the app was presented as important for some of the Australian older people interviewed in Bhattarai’s study of older people using an app for chronic arthritic pain [ 25 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review showed that out of 279 identified pain self-management applications, only 8.2% included health care providers in the development process [ 42 ]. Studies have shown that health care providers are generally positive towards digital health applications for chronic diseases, including chronic pain [ 47 50 ]. Despite interest in and positive attitudes towards eHealth solutions, few health care providers recommend the use of applications (apps) or digital solutions to their patients [ 48 , 51 ], and the overall use of eHealth solutions in health care services is limited [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%